Microporous layer material as well as preparation method and application thereof

By plasma treatment and N and S co-doping of carbon paper, a microporous layer material resistant to high-potential corrosion was prepared, which solved the corrosion problem of microporous layers in fuel cells under high temperature, high humidity and high potential conditions, and improved the durability and water management performance of fuel cells.

CN121076154APending Publication Date: 2025-12-05DEQING COUNTY ZHEJIANG UNIV OF TECH MOGANSHAN RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511032487.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing microporous layer materials for fuel cells are prone to electrochemical corrosion under high temperature, high humidity and high potential conditions, which affects their durability and water management capabilities.

Method used

By plasma treatment of carbon paper, hydrophilicity and defect structures are introduced. Then, carbon materials co-doped with N and S elements are mixed with conductive carbon black and PTFE to form a microporous slurry. After coating the carbon paper surface, high-temperature heat treatment is performed to construct a hydrophilic/hydrophobic dual-channel and gradient change structure.

Benefits of technology

It significantly improves the corrosion resistance and water management capabilities of the microporous layer, extends the service life of the fuel cell, and optimizes the internal water and thermal management of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121076154A_ABST
    Figure CN121076154A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of fuel cells, and particularly relates to a microporous layer material as well as a preparation method and application thereof. The method comprises the following steps: S.1, treating carbon paper, hydrophilizing the surface of the carbon paper, and introducing a defect structure; s.2, weighing a certain mass of organic matter as a nitrogen source, a sulfur source or a boron source, adding deionized water, uniformly stirring, obtaining a precursor by a hydrothermal method, and sintering the precursor at a high temperature for a certain time to obtain a heteroatom-doped carbon material; s.3, mixing conductive carbon black powder with the carbon material and PTFE in the step S.2, fully mixing the mixture through mechanical stirring, then adding a solvent, performing ultrasonic stirring, then adding a water repellent agent, performing ultrasonic stirring, and fully fusing the mixture to obtain microporous layer slurry; and S.4, uniformly coating the surface of the treated carbon paper with the slurry obtained in the step S.3, and placing the coated carbon paper in a drying oven for high-temperature heat treatment. The corrosion resistance of the gas diffusion layer under high potential is improved, the service life is prolonged, and the construction and gradient change structure of hydrophilic / hydrophobic double channels in the GDL is realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of fuel cells, and particularly relates to a microporous layer material and a preparation method and application thereof. BACKGROUND

[0002] Fuel cells have great potential in both efficiency and environmental protection, compared with traditional internal combustion engines, fuel cells can use hydrogen as fuel to reduce pollution, fuel cells can directly convert the energy in hydrogen into electricity, which is not affected by Carnot cycle, and the conversion efficiency can reach about 60%. Proton exchange membrane fuel cell (PEMFC) belongs to low-temperature fuel cell, which has low operating temperature and high energy conversion efficiency, and is one of the devices most likely to replace traditional energy devices. Gas diffusion layer (GDL) as one of the key materials, is composed of microporous layer and substrate layer, the microporous layer is a material with microporous structure, which is used to improve the interface between the catalyst layer and the substrate layer, and provide gas transmission and water vapor generated by reaction to discharge, so the microporous layer has important influence on the power performance and water management performance of fuel cells.

[0003] Durability has been a key factor hindering the development of fuel cells for many years. Improving the corrosion resistance of fuel cells can allow them to run smoothly for a longer period of time, thereby increasing their effective service life. Yan et al. proposed in the paper Effect of sub-freezing temperatures on a PEM fuel cell performance, startup and fuel cell components that when fuel cells work at low temperatures, the water vapor transport capacity is reduced due to the destruction of the PTFE coating on the surface of the gas diffusion layer, which in turn affects the durability. With the strict requirements for the durability of fuel cells, the corrosion resistance of the microporous layer is particularly important. Currently, the corrosion of the microporous layer mainly manifests as the oxidation corrosion of carbon at high potential and the loss of PTFE, which leads to the destruction of the microporous layer structure and affects the hydrophobicity of the gas diffusion layer, causing its water management ability to decline. Hou et al. obtained in the paper Enhanced performance of proton exchange membrane fuel cell by introducing nitrogen-doped CNTs in both catalyst layer and gas diffusion layer that the corrosion resistance of the microporous layer can be improved by doping N elements in the microporous layer, thereby improving the performance of the fuel cell. Plasma treatment introduces defects and changes the surface structure of carbon materials through the interaction of high-energy particles with the surface of carbon materials, thereby increasing the active sites of the materials and enhancing their chemical activity. Zhao et al. believed in the paper Graphene modification based on plasma technologies. that high-energy particles in non-equilibrium plasma can react with any node in carbon materials, forming new chemical bonds or changing the original bonding state. This structural modification not only improves the surface energy of the material, but also enhances its interaction ability with the corrosion medium.

[0004] In the patent CN110165241A A kind of fuel cell corrosion-resistant microporous layer based on graphitization carbon and its preparation method, the suspension slurry consisting of graphitization carbon, polytetrafluoroethylene, alcohol solvent is uniformly deposited on carbon paper by spraying method, then dried, high temperature heat treatment can be carried out. The invention overcomes the deficiencies of the prior art, such as poor corrosion resistance of commonly used conductive carbon black materials, inability to accurately control carbon loading and carbon distribution by screen printing and blade coating, etc. The microporous layer prepared by the above method has excellent performance, which greatly improves the corrosion resistance and water vapor transport capacity of the gas diffusion layer of the fuel cell. However, the invention only modifies carbon and does not study the role of multiple materials in the preparation of fuel cell corrosion-resistant microporous layer. The research material is too single.

[0005] In the patent CN119381463A, a preparation method and application of a fuel cell gas diffusion layer, a gas diffusion layer is prepared through a series of steps such as hydrophilic treatment, sulfonic acid soaking, hydrophobic treatment and microporous layer coating. In this technical solution, the plasma treatment in the hydrophilic treatment is placed first, which does not affect the hydrophobic performance of the hydrophobic material; the sulfonic acid has weak corrosiveness and will not corrode and damage the equipment; the technical defects of strong corrosiveness and poor hydrophilic performance in the existing technology for preparing a gas diffusion layer with both hydrophobic and hydrophilic properties are solved. However, the invention only uses plasma treatment for hydrophilic treatment, and the treatment method is single.

[0006] The present application is tested under simulated fuel cell actual working conditions, and it is found that the microporous layer prepared by the present technology can effectively improve the corrosion resistance of the gas diffusion layer under high potential conditions, further prolong the service life under actual dynamic working conditions, and realize the construction of the hydrophilic / hydrophobic double channel and the gradient change structure in the GDL, which can further optimize the water and heat management in the battery, and provide an important technical basis for the durability research of the subsequent proton exchange membrane fuel cell. SUMMARY

[0007] In order to overcome the defect that the microporous layer in the gas diffusion layer is mainly composed of carbon powder and is easy to be electrochemically corroded under high temperature, high humidity and high potential conditions, a microporous layer material and its preparation method and application are provided.

[0008] The specific technical scheme of the present application is as follows:

[0009] The present application provides a preparation method of a microporous layer material, comprising the following steps:

[0010] S.1. treating the carbon paper to make its surface hydrophilic and introduce defect structure;

[0011] S.2. weighing a certain amount of organic matter as a nitrogen source, a sulfur source or a boron source, adding deionized water and stirring uniformly, hydrothermally obtaining a precursor, and sintering the precursor at high temperature for a certain time to obtain a heteroatom-doped carbon material;

[0012] S.3. mixing conductive carbon black powder with the carbon material in step S.2 and PTFE, fully mixing them by mechanical stirring, then adding a solvent and ultrasonic stirring, and then adding a hydrophobic agent and ultrasonic stirring to make them fully integrated, to obtain a microporous layer slurry;

[0013] S.4. uniformly coating the slurry obtained in step S.3 on the surface of the treated carbon paper, and placing the coated carbon paper in an oven for high-temperature heat treatment.

[0014] Further, the method for treating the carbon paper in step S.1 includes gas-phase plasma treatment, oxidation treatment and liquid-phase glow discharge.

[0015] Further, the nitrogen source comprises glucose, melamine; the sulfur source comprises thiourea, polystyrene sulfonic acid; the boron source comprises boric acid, boric anhydride.

[0016] Further, the precursor is heated to 600-1000℃, and the sintering time is 1-5h.

[0017] Further, the conductive carbon black powder in the step S.3 comprises acetylene black, ketjen black, BP2000, XC-72.

[0018] Further, the mixing mass ratio of the conductive carbon black powder, the carbon material and the PTFE is 1:1:1-3:1:1, the mechanical stirring time is 10-30min, the solvent comprises deionized water, ethanol, isopropanol and other organic solvents, the ultrasonic stirring time after adding the solvent is 10-60min, the ultrasonic stirring time after adding the hydrophobic agent is 10-60min, and the viscosity range of the slurry is 1000-4500mpa.s.

[0019] Further, the thickness range of the slurry in the step S.4 is 50-150μm, and the oven temperature range is 200-500℃.

[0020] In the second aspect, the application provides a microporous layer material prepared by the above method.

[0021] In the third aspect, the application provides an application of the microporous layer material in preparing a fuel cell resistant to high potential corrosion.

[0022] Further, the single cell with the best performance is prepared by taking the plasma+CNS GDL as a cathode.

[0023] The beneficial effects of the application mainly include:

[0024] (1) The carbon paper is first subjected to plasma treatment to cause defects on the surface of the carbon paper and improve the potential corrosion resistance thereof, and the microporous layer slurry is subjected to co-doping modification treatment of N and S elements to form new coordination bonds and active sites, enhance the π-π conjugated structure of the material, and thus improve the electronic transfer capacity and corrosion resistance thereof; then the microporous layer slurry is semi-permeated into the carbon paper layer through a specific coating method to prepare a new material, a gas diffusion layer with gradient change in structure, and the corrosion resistance of the gas diffusion layer is tested by electrochemical corrosion test to compare the corrosion resistance difference between the gas diffusion layer and a common gas diffusion layer.

[0025] (2) The technical solution is suitable for any gas diffusion layer coated with a microporous layer, fills the gap in the preparation of the microporous layer resistant to high potential corrosion in the proton exchange membrane fuel cell, realizes the construction of the hydrophilic / hydrophobic double channel in the GDL and the gradient change structure, and provides a technical basis for further improving the durability of the microporous layer and prolonging the effective service life of the proton exchange membrane fuel cell.

[0026] (3) The method is simple to operate and low in cost, and is conducive to wide application in industrial production. BRIEF DESCRIPTION OF DRAWINGS

[0027] Figure 1 The chronopotentiogram of the comparative example of Example 1 is shown in the figure;

[0028] Figure 2 The chronopotentiogram of the comparative example of Example 2 is shown in the figure;

[0029] Figure 3 The element distribution (Mapping) of the carbon material in Examples 1 and 2 is shown in the figure;

[0030] Figure 4 The chronopotentiogram of the comparative example of Example 3 is shown in the figure;

[0031] Figure 5 The single cell polarization curve comparison figure of Examples 1, 2, 3 and the comparative example is shown in the figure;

[0032] Figure 6 The high-frequency impedance comparison figure of Examples 1, 2, 3 and the comparative example is shown in the figure;

[0033] Figure 7 The AC impedance comparison figure of Examples 1, 2, 3 and the comparative example at high current density is shown in the figure. DETAILED DESCRIPTION

[0034] The following describes the embodiments of the present application through specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the disclosure in the specification. The present application can also be implemented or applied by different specific embodiments, and the details in the specification can be modified or changed based on different views and applications without departing from the spirit of the present application. It should be noted that the following examples and features in the examples can be combined with each other without conflict. The methods used in the examples of the present application are conventional methods, and the reagents used can be obtained from commercial channels.

[0035] Example 1: A preparation method of a new type of microporous layer material resistant to high potential corrosion and durability test

[0036] 1. Experimental steps:

[0037] Step 1, plasma treatment of carbon paper, the specific treatment conditions include power input of 300W, using air as the environmental gas, introducing oxygen-containing groups to the surface of the material, making the surface hydrophilic, the gas flow is controlled at 10L / min, the treatment time is 300s.

[0038] Step 2, weigh 9g melamine and 1g polystyrene sulfonic acid, add deionized water and stir until uniform, then obtain the precursor by hydrothermal method. Put the precursor in a tube furnace and sinter at 900℃ for 2h to obtain N, S co-doped carbon nanosheet (CNS).

[0039] Step 3, mix acetylene black with CNS and PTFE in a ratio of 1.5:1:1, mix them thoroughly by mechanical stirring for 30min, then add a certain amount of deionized water, stir and ultrasonic for 30min, then add polytetrafluoroethylene (PTFE) and stir and ultrasonic for another 30min, so that they are fully integrated, and control the viscosity to be 3500mpa.s, to obtain the microporous layer slurry.

[0040] Step 4, uniformly coat the above slurry on the surface of the treated carbon paper, and control the thickness to be 100μm, then put the coated carbon paper in a 250℃ oven for high-temperature heat treatment to obtain a new type of GDL.

[0041] Step 5, determination of the durability of the microporous layer: in the traditional three-electrode system, use pH=3 H2SO4 solution as the electrolyte, glass slide as the auxiliary electrode, and saturated calomel electrode as the reference electrode, conduct constant potential off-line corrosion test on the new type of GDL at 1.5V (vs. RHE), compare the corrosion current density of the new type of GDL with that of ordinary GDL under the same conditions, and analyze the difference in corrosion resistance, and compare the contact angle and four-probe resistivity of the GDL before and after corrosion.

[0042] 2. Results analysis:

[0043] As Figure 1 , Table 1, in the 10h high potential durability test, the new type of GDL prepared in this embodiment starts to stabilize at about 1000s, and the corrosion current density remains at 0.01μA·cm -2 , which significantly improves the durability of the fuel cell compared with the ordinary GDL; in addition, the attenuation rate of the new type of GDL in terms of hydrophilicity and hydrophobicity and resistivity is obviously improved after high potential corrosion, which means that the water management ability and internal resistance of the fuel cell using the new type of GDL are further optimized during actual operation.

[0044] Table 1 Comparison of contact angle and four-probe resistivity of the comparative example before and after electrochemical corrosion

[0045]

[0046] Example 2: Influence of plasma treatment on the durability of microporous layer material

[0047] The microporous layer durability test method of Example 2 is consistent with that of Example 1, and in the constant potential test at 1.5V, the GDL prepared in this example reaches a stable state at about 2000s, and the corrosion current density is stable at 0.3μA.cm Figure 2 , Table 2. The GDL prepared in this example reaches a stable state at about 2000s, and the corrosion current density is stable at 0.3μA.cm -2 , and, as Figure 3 In both hydrophilicity and hydrophobicity and resistivity, it is better than ordinary GDL, but compared with the new type of GDL in Example 1, it is still relatively inferior. Figure 3 The element distribution map of the microporous layer slurry dopant "N, S co-doped carbon nanosheet (CNS)" under the electron microscope, C, N, S in the upper left corner of the figure represent the distribution of carbon, nitrogen and sulfur three elements, it can be seen that the three elements C, N and S in the dopant are uniformly distributed, which means that the carbon nanosheet is successfully synthesized, and then the carbon nanosheet is mixed with carbon powder to prepare a microporous layer slurry, which is coated on the surface of carbon paper, and a GDL doped with N and S elements can be successfully prepared. The representation method of this GDL is "CNS GDL".

[0048] Table 2 Comparison table of contact angle and four-probe resistivity of comparative samples before and after electrochemical corrosion

[0049]

[0050] Example 3: Influence of slurry modification treatment on the durability of microporous layer material

[0051] The microporous layer durability test method of Example 2 is consistent with that of Example 1, and in the constant potential durability test at 1.5V, 10h, the GDL prepared in this example reaches a stable state at about 1600s, and the corrosion current density is stable at 0.05μA.cm Figure 4 , Table 3. The GDL prepared in this example reaches a stable state at about 1600s, and the corrosion current density is stable at 0.05μA.cm -2 , compared with ordinary GDL and the GDL in Example 2, the microporous layer surface of the GDL treated by plasma has better high potential corrosion resistance.

[0052] Table 3 Comparison table of contact angle and four-probe resistivity of comparative samples before and after electrochemical corrosion

[0053]

[0054] Example 4: Selection of battery

[0055] In combination with Figure 5From the current density-voltage (polarization) curves, we found that the single cell prepared by "plasma + CNS GDL" as the cathode has a slow voltage drop (small polarization), indicating that it has low internal resistance, fast reaction kinetics, strong mass transfer capability, and can effectively maintain high voltage output.

[0056] Combination Figure 6 From the current density-resistance curves, we found that single cells fabricated using "plasma + CNS GDL" as the cathode exhibit low HFR and high current density. A low HFR indicates high membrane proton conductivity, good module contact, and low electron transport loss, which is beneficial for sufficient membrane hydration and appropriate module assembly pressure. Furthermore, the stable curve indicates the absence of membrane dehydration, chemical degradation, or module damage, making it suitable for a wide range of applications.

[0057] Combination Figure 7 From the real-imaginary impedance diagram, we found that the single cell prepared with "plasma + CNS GDL" as the cathode has the best impedance performance, low internal resistance, low energy loss, and good output voltage stability.

[0058] Therefore, the single cell prepared using "plasma + CNS GDL" as the cathode exhibits the best performance, outperforming the other three samples to varying degrees.

Claims

1. A method for producing a microporous layer material, characterized by, The method comprises the following steps: S.

1. treating the carbon paper to make its surface hydrophilic and introduce defect structure; S.

2. weighing a certain amount of organic matter as nitrogen source, sulfur source or boron source, adding deionized water and stirring uniformly, hydrothermally obtaining a precursor, and sintering the precursor at high temperature for a certain time to obtain a heteroatom-doped carbon material; S.

3. mixing the conductive carbon black powder with the carbon material in step S.2 and PTFE, fully mixing them by mechanical stirring, then adding a solvent and ultrasonic stirring, and then adding a hydrophobic agent and ultrasonic stirring to make them fully integrated, to obtain a microporous layer slurry; S.

4. uniformly coating the slurry obtained in step S.3 on the surface of the treated carbon paper, and placing the coated carbon paper in an oven for high-temperature heat treatment.

2. A method of making a microporous layer material according to claim 1, wherein, The method for treating the carbon paper in step S.1 includes gas-phase plasma treatment, oxidation treatment, and liquid-phase glow discharge.

3. The method of claim 1, wherein the microporous layer material is prepared by a process comprising: The nitrogen source includes glucose and melamine; the sulfur source includes thiourea and polystyrene sulfonic acid; and the boron source includes boric acid and boric anhydride.

4. The method of claim 1, wherein the microporous layer material is prepared by a process comprising: The precursor is heated to 600-1000℃ at high temperature, and the sintering time is 1-5h.

5. The method of claim 1, wherein the microporous layer material is prepared by the steps of: The conductive carbon black powder in step S.3 includes acetylene black, ketjen black, BP2000, and XC-72.

6. A method of making a microporous layer material according to claim 5, wherein, The mixing mass ratio of the conductive carbon black powder, the carbon material, and PTFE is 1:1:1-3:1:1, the mechanical stirring time is 10-30min, the solvent includes deionized water, ethanol, and isopropanol, the ultrasonic stirring time after adding the solvent is 10-60min, the ultrasonic stirring time after adding the hydrophobic agent is 10-60min, and the viscosity of the slurry ranges from 1000 to 4500mpa.s.

7. The method of claim 1, wherein the microporous layer material is prepared by a process comprising: The thickness of the slurry in step S.4 ranges from 50 to 150μm, and the oven temperature ranges from 200 to 500℃.

8. A microporous layer material prepared by the method of any one of claims 1-7.

9. Use of the microporous layer material of claim 8 in the preparation of a fuel cell resistant to high-potential corrosion.

10. Use according to claim 9, wherein The single cell with the best performance is prepared by using the plasma+CNS GDL as the cathode.

Citation Information

Patent Citations

  • Corrosion-resistant microporous layer for fuel cell based on graphitized carbon and preparation method of corrosion-resistant microporous layer

    CN110165241A

  • Preparation method and application of fuel cell gas diffusion layer

    CN119381463A